Wittig reactions of maleimide-derived stabilized ylides with alkyl pyruvates: concise approach to methyl ester of (+/-)-chaetogline A - Shelar, Santosh V.; Argade, Narshinha P. (Synthesis-Stuttgart, 2021)
A facile synthesis of methyl ester of chaetogline A is reported starting from the corresponding methyl 1-methyltryptophanate-derived- maleimide. A stereoselective Wittig olefination with a carbonyl function in methyl pyruvate followed by phosphorous pentoxide-induced- regioselective dehydrative cyclization are the essential reactions. An acid-induced thermodynamically driven stereoselective beta- to alpha-position migration of the exocyclic C=C bond unit in ethyl tetrahydroindolizinoindolylidenepropanoate is described.
Keywords: Amino acid; chaetogline A; dehydrative cyclization; maleimide; methyl pyruvate; Natural product; Wittig reaction

Wittig reactions of maleimide-derived stabilized ylides with alkyl pyruvates: concise approach to methyl ester of (±)-chaetogline A - Argade, Narshinha P.; Shelar, Santosh V. (Synthesis, 2021)
A facile synthesis of methyl ester of chaetogline A is reported starting from the corresponding methyl 1-methyltryptophanate-derived maleimide. A stereoselective Wittig olefination with a carbonyl function in methyl pyruvate followed by phosphorous pentoxide-induced regioselective dehydrative cyclization are the essential reactions. An acid-induced thermodynamically driven stereoselective β- to α-position migration of the exocyclic C=C bond unit in ethyl…